The management of sexually transmitted infections by Australian general practitioners. Issue 3 (28th May 2004) - Johnston, V J; Britt, H; Pan, Y; Mindel, A
Abstract : Objectives: To ascertain how frequently general practitioners (GPs) in Australia encounter sexually transmitted infections (STIs), how STIs are managed in general practice, and the characteristics of GPs who manage STIs. Methods: Data were derived from the Bettering the Evaluation and Care of Health (BEACH) database. BEACH is a cross sectional survey of national GP activity. Approximately 1000 GPs per year each record details of 100 consecutive patient encounters. Details from April 1998 to March 2001 about frequency and pattern of STIs managed and the characteristics of GP managing them were analysed using SAS. Results: 3030 GPs provided data on 303 000 encounters. Only 521 problems managed were STIs. Viral STIs were most frequently managed including genital herpes (0.08 per 100 encounters), genital warts (0.07 per 100 encounters). Gonorrhoea, syphilis, chlamydia, and trichomoniasis were rarely managed. Medication was prescribed at a rate of 56.1 per 100 STI contacts (95% CI 50.4 to 61.7). Antivirals were the most common followed by topical chemotherapeutics. GPs managing STIs were significantly younger and more likely to be female, urban, have fewer years in practice, work fewer sessions a week, work in a larger practice, have graduated in Australia, and hold the FRACGP (all p<0.005) than those who did not. Conclusion: Management of diagnosed STIs forms only a small part of a GP's workload in Australia. Genital herpes and warts are the most commonly managed conditions. GPs managing STIs are different from those who do not. Strategies to improve diagnosis, management, and screening should be evaluated.